Abrupt Changes in the Subpolar North Atlantic and Their Impact on the Climate of the British Isles - Matthew B. Menary; Laura C. Jackson; Richard A. Wood; Richard A. Betts (Geophysical Research Letters)
Abstract There has been increasing interest in the possibility of abrupt climatic changes in the North Atlantic and their impacts on northwestern Europe. Here, we investigate such abrupt changes in a large ensemble of CMIP6 climate models. We define two potentially observable metrics based on subpolar sea surface temperatures (SSTs) or mixed layer depths (MLDs), to explore the link between temperature changes and convection collapse. The two metrics yield similar numbers of abrupt events but suggest that several types of abrupt event are possible. Abrupt MLD changes appear related to ongoing warming. Abrupt SST changes mostly consist of decadal cooling followed by warming, apparently related to coupled dynamics involving the North Atlantic Oscillation (NAO). Models with more realistic NAO variability show more such events. However, several more persistent SST events are also found. Both cooling and warming phases have important implications for impacts and adaptation, particularly over the British Isles.